Radiological study on disc degeneration of thoracolumbar burst fractures treated by percutaneous pedicle screw fixation - Wang, Jian (Springer-Verlag, 2012)
OBJECTIVE: To examine disc degeneration at levels adjacent and next adjacent to the fractured vertebra and to analyses, if the disc degeneration is determined by the endplate fracture. SUMMARY OF BACKGROUND DATA: Thoracolumbar burst fracture is one of the most common spinal injuries. The diagnostic (clinical and imaging) approach and treatment of a fractured vertebra is well established; however, some controversy remains. The associated disc degeneration is less well known after 9–12 months of the short segment pedicle screw fixations. There is a major controversy whether spinal trauma with vertebral endplate fractures can result in posttraumatic disc degeneration. No study to date, however, has assessed disc degeneration of the AO type A3 thoracolumbar fractures without neurologic deficits after pedicle screw fixations. METHODS: Twenty-six patients with single-level AO type A3 thoracolumbar fractures and no neurological deficit were treated by using postural reduction and short segment percutaneous pedicle screw fixation. No laminectomy and fusion were performed. Implants were removed 9–12 months after the first operation. The thoracolumbar magnetic resonance imaging (MRI) was used to assess disc degeneration at levels adjacent and next adjacent to the fractured vertebra before the first operation and after the second operation in a retrospective study. RESULTS: After the instrumentation removal, new disc degeneration was usually found at level adjacent to the cranial endplate of fractured vertebra by MRI examination in 24 patients. The average Pfirrmann grade of degenerative discs adjacent to the cranial fractured endplates deteriorated from 2.1 pre-operatively to 3.4 after the second operation. No change of disc degeneration was seen at the caudal disc space adjacent to the fractured vertebra and the levels next adjacent to the fractured vertebra. The discs next adjacent to the fractured vertebra were showed to be relatively normal without changes of degeneration during the study period. CONCLUSIONS: Disc degeneration usually occurs at level adjacent to the fractured endplate of thoracolumbar burst fractures. Endplate fracture is strongly associated with disc degeneration. No correlation between fixation level and disc degeneration is seen in this study.